Effect of light and temperature on seed germination in guava (Psidium guajava L. - Myrtaceae) - Sugahara, V. Y. [UNESP]; Takaki, M. [UNESP] (International Seed Testing Association, 2004)
The germination of seeds of Psidium guajava L. (Myrtaceae) is controlled by phytochrome. Guava seeds can germinate with at least one hour per day of irradiation of high red:far-red ratio light preceeded or followed by shade light, indicating that phytochrome B controls germination in these conditions. Under alternating temperatures, in a range of at least 5°C, seeds will germinate in darkness, suggesting that in gaps of the canopy, when seeds are covered by a thin layer of soil they will germinate once the alternating temperatures are experienced. Under these conditions phytochrome A is responsible for the control of guava seed germination.